A randomised clinical study to evaluate the effect of brushing duration on fluoride levels in dental biofilm fluid and saliva in children aged 4–5 years. (December 2013) - Newby, Evelyn E.; Martinez‐Mier, Esperanza A.; Zero, Domenick T.; Kelly, Sue A.; Fleming, Nancy; North, Mairead; Bosma, Mary Lynn
Abstract : Objectives: To compare the effect of 40 seconds versus 2 minutes brushing on saliva and dental biofilm fluid fluoride in children ages 4–5 years over 1 hour. Design: This was a single‐blind, cross‐over, randomised, two‐period clinical study in healthy children. Three days before the start of each treatment subjects received a thorough brushing and then refrained from all oral hygiene procedures. At treatment visits, after collecting baseline biofilm and saliva samples, staff brushed the occlusal surfaces of the subject's posterior teeth with a pea‐sized amount (0.25 g) of NaF/silica toothpaste for the randomised time. Samples were taken at 5 minutes, 15 minutes, 30 minutes and 60 minutes after brushing and analysed for fluoride using a microanalytical methodology. There was a minimum 4‐day washout period between treatments. Results: Log changes from baseline biofilm fluid and saliva fluoride were statistically significant ( P < 0.05) for both brushing times at all post‐brushing time‐points [except 60 minutes saliva where P = 0.06 ( t ‐test)]. Statistically significantly greater ln‐AUC (area under the curve) was found for biofilm fluid and salivary fluoride after brushing for 2 minutes compared with brushing for 40 seconds over the 1‐hour test period. There was a statistically significantly higher concentration of fluoride in the log change from baseline saliva levels after 5, 15, 30 and 60 minutes for the 2‐minute brushing time compared with 40 seconds brushing time. There was no statistically significant difference in concentration of log change from baseline fluoride levels in biofilm fluid at each individual time‐point (5, 15, 30 and 60 minutes) for the 2‐minute brushing time compared with the 40‐second brushing time, but significant differences were observed for 15, 30 and 60 minutes in favour of 2‐minute brushing time when log biofilm fluid value was analysed. Conclusion: The findings provide further evidence for the benefits of increased duration of brushing with respect to fluoride delivery.